PENGUATAN PEMAHAMAN KEAGAMAAN PADA PESERTA DIDIK DAN TENAGA PENDIDIK DALAM PENINGKATAN MOTIVASI ENTERPRENEUR SYARIAH (PADA PESANTREN DARUL I’TISHAM JENEPONTO) - Munawir K; Rofiqah Almunawwarah; Ismawati; Ayu Rezki Sulfiana; Asmila Dewi; Nurjannah (Universitas Islam Negeri Alauddin Makassar, 2023)
This research aims to increase sharia entrepreneurial motivation among students and teaching staff at the Darul I'Tisham Jeneponto Islamic Boarding School. The improvement efforts made are by strengthening religious understanding through socialization and Focus Group Discussions (FGD). This research is a type of qualitative and quantitative research (mix-methods). This research is a form of grounded research using the Participation Action Research (PAR) technique. Meanwhile, the quantitative method used in this research is the experimental method and data processing using the paired sample t test. The results of the research show that the role of holding socialization and FGDs includes strengthening understanding of entrepreneurship in Islam, the importance of entrepreneurship, introducing sharia entrepreneurship, and there is a comparison of the influence before and after holding socialization activities and FGDs on the motivation of sharia entrepreneurship among Islamic boarding school students and teaching staff. Darul I'Tisham.